A review on macro-encapsulated phase change material for building envelope applications. (15th October 2018) - Liu, Zhengxuan; Yu, Zhun (Jerry); Yang, Tingting; Qin, Di; Li, Shuisheng; Zhang, Guoqiang; Haghighat, Fariborz; Joybari, Mahmood Mastani
Abstract: Integrating phase change material (PCM) into building envelopes significantly reduces building energy consumption and improves indoor environment. Among different integration techniques, macro-encapsulation allows for an efficient, safe and convenient way of using PCM, and its applications have been widely investigated in recent years. However, this study argues that there is a lack of a systematic analysis regarding the thermal performance of macro-encapsulated PCM, particularly for building envelope applications. Also, a number of important issues have seldom been addressed such as material selection and PCM melting processes at a component level, and optimal locations at a system level. Such a research gap remains a barrier to architects and engineers succeeding at making rational decisions during building design stages, thereby achieving the optimal building performance. This paper aims to provide a comprehensive overview of macro-encapsulated PCM and its integration into building envelopes. The discussion mainly includes: definition and material selection for PCM macro-encapsulation, common macro-encapsulation forms and PCM melting processes within these forms, the optimal locations of systems in building envelopes, and thermal performance enhancement for PCM and shells. In addition, the key issues in future studies are discussed. It is hoped that this comprehensive review will contribute to a deeper understanding of the design and application of macro-encapsulated PCM in building envelopes. Highlights: Comprehensive review on macro-encapsulated PCM in building envelopes. Definition and material selection for PCM macro-encapsulation. Common macro-encapsulation forms and PCM melting processes within these forms. Thermal performance enhancement for macro-encapsulated PCM.